Гибкие методологии управления образовательными проектами - Лукьянов, Дмитрий Владимирович; Гогунский, Виктор Дмитриевич; Колесников, Алексей Евгеньевич; Олех, Татьяна Мефодиевна (НТУ "ХПИ", 2017)
Предложены подходы совершенствования базовых концептов проактивного управления обучением на основе инновационных программ профессионального обучения. Показано, что в условиях сокращения жизненного цикла знаний трансформация "Конуса в образовании" Эдгара Дейла к модели "Воронки знаний" и гибким методологиям управления проектами позволяет реализовать систему "обучения действием" со смещением методологии обучения в область прагматизма.

Changing the paradigm of modern professional education is related to the problem of the competence training – how to provide the required level of training to competence which would be formed and applied in practice, "here and now". This problem can be solved by creating short-term training programs or medium-term programs aimed at the acquisition of new competencies on the basis of previously obtained qualification, up to conversion professionals to transition a new profession. This article deals with improvement of the basic concepts of proactive learning management. The bases of these concepts are innovative training programs. It is shown that in the conditions when the life cycle of knowledge is reduced, the transformation of "Cone of education" by Edgar Dale to the model of the "Funnel of knowledge", and the usage of flexible project management methodologies allows to implement a system of "learning by doing" with a shift of training methodologies to the pragmatism.
Flexible project management methodology in education
Keywords: управление проектами; конус информации; период полураспада компетенций; темпомиры; гибкие методологии; project management; cone of information; half-life competencies; tempo-world; learning by doing; project-based learning; flexible project; management methodologies; DSDM; lifelong learning